An economic evaluation of the randomized controlled trial of topical corticosteroid and home‐based narrowband ultraviolet B for active and limited vitiligo (the HI‐Light Vitiligo Trial). (1st May 2021) - Sach, T.H.; Thomas, K.S.; Batchelor, J.M.; Perways, A.; Chalmers, J.R.; Haines, R.H.; Meakin, G.D.; Duley, L.; Ravenscroft, J.C.; Rogers, A.; Santer, M.; Tan, W.; et al.
Summary: Background: Economic evidence for vitiligo treatments is absent. Objectives: To determine the cost‐effectiveness of (i) handheld narrowband ultraviolet B (NB‐UVB) and (ii) a combination of topical corticosteroid (TCS) and NB‐UVB compared with TCS alone for localized vitiligo. Methods: Cost‐effectiveness analysis alongside a pragmatic, three‐arm, placebo‐controlled randomized controlled trial with 9 months' treatment. In total 517 adults and children (aged ≥ 5 years) with active vitiligo affecting < 10% of skin were recruited from secondary care and the community and were randomized 1: 1: 1 to receive TCS, NB‐UVB or both. Cost per successful treatment (measured on the Vitiligo Noticeability Scale) was estimated. Secondary cost–utility analyses measured quality‐adjusted life‐years using the EuroQol 5 Dimensions 5 Levels for those aged ≥ 11 years and the Child Health Utility 9D for those aged 5 to < 18 years. The trial was registered with number ISRCTN17160087 on 8 January 2015. Results: The mean ± SD cost per participant was £775 ± 83·7 for NB‐UVB, £813 ± 111.4 for combination treatment and £600 ± 96·2 for TCS. In analyses adjusted for age and target patch location, the incremental difference in cost for combination treatment compared with TCS was £211 (95% confidence interval 188–235), corresponding to a risk difference of 10·9% (number needed to treat = 9). The incremental cost was £1932 per successful treatment. The incremental difference in cost for NB‐UVB compared with TCS was £173 (95% confidence interval 151–196), with a risk difference of 5·2% (number needed to treat = 19). The incremental cost was £3336 per successful treatment. Conclusions: Combination treatment, compared with TCS alone, has a lower incremental cost per additional successful treatment than NB‐UVB only. Combination treatment would be considered cost‐effective if decision makers are willing to pay £1932 per additional treatment success.